The Implementation of Islamic Religious Education in Shaping the Religious Character of Elementary School Students - Eko Prayetno; Ibnu Imam Al Ayyubi; Muhammad Ageng Rahayu; Azka Rahmawati; Brilliant Windy Khairunnisa (Al-Bustan: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the differences in final grades for Islamic Religious Education at SMP Negeri 3 Kendari and MTs Asy-Syafi'iyah Kendari in classes VIII A, VIII B, and VIII C, as well as to identify the impact of gender on students' learning outcomes. The study employs a quantitative approach with descriptive analysis, normality test, homogeneity test, and Two-Way ANOVA. The results show a significant difference in final PAI grades between class VIII A and VIII C, as well as between VIII B and VIII C, but no significant difference between VIII A and VIII B. Additionally, a significant difference in final PAI grades was found between male and female students, although there was no significant interaction between the class and gender. The data used was normally distributed but not homogeneous, thus further Post Hoc testing was conducted. These findings suggest that variations in PAI learning outcomes are influenced by the school environment and the teaching characteristics in each class.